Polska w strefie euro? Trzy scenariusze i ich prawdopodobne konsekwencje ogólnoekonomiczne - Götz, Marta; Nowak, Bartłomiej E.; Orłowski, Witold M. (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
Dyskusje i badania polskiego członkostwa w strefie euro są w obecnych, dynamicznie zmieniających się warunkach obarczone dużą dozą niepewności, stąd ograniczać się mogą jedynie do kreślenia scenariuszy. Niniejsze opracowanie skupia się na aspektach gospodarczych decyzji o: 1) definitywnej rezygnacji z wprowadzenia wspólnej waluty w Polsce, 2) szybkiej akcesji do strefy euro oraz 3) odsunięciu w czasie udziału Polski w tej strefie. Każdy z wariantów rodzi inne skutki polityczno-ekonomiczne i tym samym wyznacza inne ścieżki długookresowego rozwoju polskiej gospodarki.

The ongoing discussion of Polish membership of the euro area seems subject to a high degree of uncertainty, caused by dynamically changing conditions. A precise and predictive analysis is therefore hampered and limited to the exploration of pos¬sible scenarios. Our study focuses on the economic aspects of decisions on: 1) definitive rejection of the single currency in Poland, 2) rapid accession to the euro area, and 3) postponement of Poland’s participation in eurozone. Each of the variants gives rise to different political and economic outcomes and thus sets different paths for the longterm development of the Polish economy.
Poland in the eurozone? Three scenarios and their probable general economic consequences
Keywords: euro; integracja europejska; unia gospodarczo-walutowa; Poland; European integration; Economic and Monetary Union